Effect of dexmedetomidine on postoperative nausea and vomiting in female patients undergoing radical thoracoscopic lung cancer resection - Zhu, Haipeng; Wang, Shichao; Wang, Ruohan; Li, Bing; Zhang, Jiaqiang; Zhang, Wei (Frontiers in Pharmacology, 2024)
Introduction: Postoperative nausea and vomiting (PONV) is a prevalent postsurgical complication. The objective of our study was to compare the effect of different doses of dexmedetomidine on PONV in female patients undergoing radical thoracoscopic lung cancer resection. Methods: A total of 164 female patients undergoing elective thoracoscopic radical lung cancer surgery were enrolled and assigned to one of four groups. Patients received 0.2 μg/kg/h, 0.4 μg/kg/h, 0.8 μg/kg/h dexmedetomidine and normal saline in the Dex1, Dex2, Dex3 and Control groups, respectively. The primary outcome was the incidence of PONV during 48 hours postoperatively. The second outcomes included the incidence of PONV and postoperative vomiting (POV) at four time points postoperatively (T1: PACU retention period; T2: PACU discharge to postoperative 12 h; T3: postoperative 12 h-postoperative 24 h; T4: postoperative 24 h-postoperative 48 h), the area under the curve of PONV grade (PONVAUC), PONV grade, POV grade and other postoperative recovery indicators. Results: The incidence of PONV differed among the four groups. The Dex2 group (29.27%) was lower than that in the Dex1 group (61.90%) and Control group (72.50%). The incidence of PONV at T2 in the Dex1 group (11.90%) and Dex2 group (9.76%) was lower than that in the Control group (42.50%). The incidence of PONV at T3 in the Dex2 group (29.27%) was lower than that in the Dex1 group (61.90%) and Control group (62.50%). The PONVAUC was lower in the Dex2 group than in the Control group. The incidence of POV at T3 in the Dex2 and Dex3 groups was lower than that in the Control group. The consumption of remifentanil, norepinephrine, PACU dwell time, VAS scores, postoperative PCA press frequency, and the time for the first postoperative oral intake were different among the four groups. The regression model shows that the Dex2 group is a protective factor for PONV. Conclusion: Dexmedetomidine can reduce the incidence of PONV and accelerate postoperative recovery in female patients undergoing radical thoracoscopic lung cancer resection. Compared with the other two dosages, 0.4 μg/kg/h dexmedetomidine is preferable. Clinical Trial Registration: chictr.org.cn, identifier ChiCTR2300071831.